Analysis of Antecedents and Consequences of Employee Career Development at PT. Krakatau Engineering Cilegon - Dewayani, Ariwinda; Saefullah, Encep; Ende, Ende (Dinasti Publisher, 2024)
The problem of career development of employees at PT. Krakatau Engineering City of Cilegon is important because career development is a process of improving a person's ability to work in order to achieve their career goals. This research aims to identify and analyze career planning, career management, career development, job satisfaction, and career commitments that can affect employees of PT. Krakatau Engineering City of Cilegon. This research using the survey method uses a quantitative approach, i.e., a questionnaire. The research's population consists of the 113 employees of P.T. Krakatau Engineering City in Cilegon. We took samples of up to 88 employees from the population using a random sampling technique. The results of this study may indicate that career planning towards career development obtained a statistical t-value of 3.144 (greater than t-table 1.96) with a path coefficient of 0.388. Career management towards career growth obtains a statistic t-value of 4.820 (greatest than t-table 1.96), with a path coefficient of 0.588. Careers development towards job satisfaction obtains a statistics t-value of 25.711 (greater than t-tabel 1.96) with a path coefficient of 0.860. Career development towards career commitment obtained the statistical t-values of 99.011 (larger than t-table 1.96) with a track factor of 0.960. The conclusion of this study is that there is an influence of career planning and career management (as an antecedent) career development, job satisfaction and career commitment (as a consequence) of employees at PT. Krakatau Engineering City of Cilegon, both partially and simultaneously.